Detection of Antimicrobial Resistant Salmonella enterica Strains in Larval and Adult Forms of Lesser Mealworm (Alphitobius diaperinus) From Industrial Poultry Farms - Donoso, Alvaro; Paredes, Natalia; Retamal, Patricio (Frontiers in Veterinary Science, 2020)
The lesser mealworms (Alphitobius diaperinus) constitute a common cosmopolitan pest in poultry flocks and may colonize the litter in adult and larval forms. Previous studies have documented their potential as carriers of enteric pathogens. In this context, S. enterica constitutes a prioritized zoonotic agent in the poultry industry due to the sanitary risks and economic losses associated with its presence. The aim of this study is to describe the presence of S. enterica strains in larval and adult forms of A. diaperinus collected from poultry litter belonging to industrial farms located in the central zone of Chile. A total of 403 specimens (203 adults and 200 larvae) were sampled from 3 farms and 25 flocks. For bacteriological isolation, beetles were processed to differentiate external and internal contamination. Then, isolates were serotyped according to the Kauffman-White scheme and antimicrobial resistance phenotypes were determined using the disk diffusion method. Gene sequences from the megaplasmid pESI were identified through a PCR based test. These procedures led to the detection of 15 S. enterica isolates, belonging to serotypes Infantis (14) and Livingstone (1), from both adults (6) and larval (9) specimens, with a similar external (7) and internal (8) distribution. Furthermore, all S. Infantis isolates showed antimicrobial resistance and evidence of megaplasmid pESI carriage, with all possessing multidrug-resistant phenotypes. Our results confirm that A. diaperinus constitutes a potential reservoir of zoonotic Salmonella strains of sanitary and economic concern for the industry and for public health.